INVESTIGATING DEBT RATIOS AND THEIR DETERMINANTS IN THE CAPITAL STRUCTURE OF INDIAN FMCG COMPANIES: AN EMPIRICAL STUDY - Priyanka; Singh, Rajbir (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This research paper investigates the determinants of capital structure within Indian FMCG companies, utilizing a representative sample of firms listed on the Bombay Stock Exchange (BSE) over a decade (2011–12 to 2020–21), sourced from the CMIE Prowess database. Employing a panel data methodology, the study evaluates indices of corporate financial leverage, including short-term debt, long-term debt, total debt, and the debt-equity ratio. The findings indicate that firm-specific variables such as size, asset tangibility, sales growth, profitability, and non-debt tax shields (NDTS) exhibit significant relationships with financial leverage in the Indian FMCG sector. Specifically, determinants of the short-term debt ratio (SDR) include firm size, age, NDTS, profitability, tangibility, and liquidity. The debt-equity ratio (DER) is significantly influenced by profitability and the effective tax rate, while total debt ratio (TDR) is associated with firm age, size, effective tax rate, asset turnover ratio, and liquidity. Additionally, long-term debt ratio (LDR) is significantly linked to firm size, asset turnover ratio, tangibility, and liquidity. The statistical analysis demonstrates that fixed effects panel regression models are the most suitable for representing SDR, LDR, TDR, and DER. Consequently, this study contributes to the existing body of knowledge on capital structure, offering empirical insights that are particularly relevant for Indian FMCG firms as they navigate financial decision-making processes informed by recent data through 2020–21.